Physical fitness and life quality of female students with different classes of diseases - Kolokoltsev, M.; Romanova, E.; Martirosova, T.; Limarenko, O.; Vorozheikin, A.; Kispayev, T. (Journal of Physical Education and Sport, 2023)
An important indicator of students' health status is the characteristic of their quality of life and physical fitness. The study of these issues in relation to the classes of diseases seems relevant and timely. Research aim: to study the female students' quality of life and physical fitness in relation to various somatic diseases. Materials and methods. The research involved 133 girls aged 17-19, who, due to their somatic health, were assigned to the 3rd functional group (special medical health group) for physical education. The female students with various classes of diseases quality of life was determined using the SF-36 questionnaire. Motor qualities were determined by testing the basic motor qualities. Results. Girls with diseases of the cardiovascular system and respiratory organs have the lowest ability to perform daily physical activity, which is associated with physical pain, low level of role functioning and general health. Girls with these diseases have the lowest characteristics of psychological health, emotional and behavioral control with the phenomena of anxiety and depression, compared with girls with other classes of diseases. Students with pathology of the cardiorespiratory system in 5 out of 7 motor tests registered the lowest indicators of testing the motor qualities of "speed", "strength", "speed-strength abilities" and "general endurance". Conclusions. Diseases of the cardiovascular and respiratory systems limit the girls' physical activity, worsen their psychological health and significantly reduce their quality of life. The results obtained should be taken into account when planning the educational process of female students' assigned to a special medical health group physical education.
Keywords: physical fitness; diseases; quality of life; motor qualities; physical education